2009
DOI: 10.1002/mnfr.200800485
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thermal processing on IgE reactivity to lentil and chickpea proteins

Abstract: In the last years, legume proteins are gaining importance as food ingredients because of their nutraceutical properties. However, legumes are also considered relevant in the development of food allergies through ingestion. Peanuts and soybeans are important food allergens in Western countries, while lentil and chickpea allergy are more relevant in the Mediterranean area. Information about the effects of thermal-processing procedures at various temperatures and conditions is scarce; therefore, the effect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 32 publications
4
45
0
2
Order By: Relevance
“…Regarding the effect of thermal treatment on lentil and chickpea seeds, our previous studies show that autoclaving at 2.6 bar for 30 min produced a significant decrease in the IgE-binding capacity of lentil and chickpea allergens, although extremely resistant immunoreactive proteins still remained in both legumes even after this heat and pressure process [24]. In this study, extreme DIC treatments produced a similar pattern of IgE-binding proteins to that observed with autoclave at harsh conditions and, therefore, a parallel reduction in the overall IgE immunoreactivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the effect of thermal treatment on lentil and chickpea seeds, our previous studies show that autoclaving at 2.6 bar for 30 min produced a significant decrease in the IgE-binding capacity of lentil and chickpea allergens, although extremely resistant immunoreactive proteins still remained in both legumes even after this heat and pressure process [24]. In this study, extreme DIC treatments produced a similar pattern of IgE-binding proteins to that observed with autoclave at harsh conditions and, therefore, a parallel reduction in the overall IgE immunoreactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that boiling in an autoclave (2.6 bar for up to 30 min) markedly reduced lupin, lentil and chickpea allergenicity [23,24]. Moreover, the use of instant controlled pressure drop (DIC®) treatment (6 bar for 3 min), combining heat and steam pressure as in autoclaving, greatly decreased IgE reactivity of the heat-resistant major lupin allergens (Lup-1 and Lup-2) [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Peanut flour was extracted according to the method reported by Cuadrado et al [12] but using 0.05 M Tris-HCl (pH 8.0) plus 0.5 N NaCl as an extraction buffer. Flour was extracted twice at a 1:10 w/v ratio for 1 h at 4°C by stirring.…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that boiling for 12 h in a closed vessel led to a 19-fold decrease of the IgE-binding capacity of peanut proteins [13]. Pressure cooking at specific conditions has also been found to impact on the IgEbinding properties of legumes [9,[14][15][16]. However, the effects of boiling or pressure cooking on soybean IgE reactivity have not yet been thoroughly explored and analyzed.…”
Section: Introductionmentioning
confidence: 99%